Reproductive medical technology: legal implications for "third gender" from Western and Islamic perspectives - Haneef, Sayed Sikandar Shah (2013)
Technological advances in the field of medicine and health sciences not only manipulate normal human body and sex but also provides for surgical cum hormonal cure for hermaphrodites, the so called “third sex”. Consequently, sex assignment surgery not only has become a standard care for babies born with genital abnormalities in the West but even in some Muslim rich nations such as Saudi Arabia. On positive side, it goes a long way in saving children born with abnormal sexual reproductive system from many legal interdictions which they experienced during pre-sex corrective surgery. The larger ethical and legal questions which it raises, however, have prompted certain states to give legal recognition to such children as “third sex”. The main issue therefore, is how to balance the child`s right to gender identity and her right against coerced reproductive corrective surgery during infancy. The paper, therefore, intends to highlight some reflections on this point particularly from Islamic legal perspective.